Peran Perpustakaan Digital UIN Datokarama Palu dalam Meningkatkan Minat Baca dan Mendukung Transformasi Perpustakaan Berbasis Inklusi Sosial - Solihin, Iramadhana (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study examines the role of the UIN Datokarama Palu digital library in enhancing students' reading interest, its impact on reading habits, and its contribution to the transformation of libraries based on social inclusion. Its novelty lies in the synergistic exploration between digital technology and the library’s social services. This research employs a mixed-method approach, combining qualitative data with quantitative data as support. The respondents include library managers, students, and the general public. The findings indicate several accessibility barriers in the digital library, such as application compatibility limitations, features that are still restricted to e-books, lack of support for disabled users, and a limited book collection. Quantitatively, no significant influence was found between digital library usage and students' reading interest. However, the library plays a role in social inclusion-based transformation through training and skill development programs, which support student empowerment. This research is expected to contribute to the development of more inclusive and efficient digital library services, as well as to enhance students' reading interest and digital literacy.